PERKEMBANGAN FUNGSI KOMERSIAL DI KAWASAN PERUMNAS BUMI TAMALANREA PERMAI MAKASSAR - , SURYADI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Residential area ideally serve to meet the needs of the community in terms of procurement of residence. However, the development of a âRukoâ for commercial activities in the area of Bumi Tamalanrea Permai Housing has been progressing from symptoms penetration trading activities became symptom invasion (invasion of a new function that is greater than the penetration phase) of commercial activity, despite the dominance of symptoms has not reached a new function. Whereas in the Spatial Plan of Makassar region Bumi Tamalanrea Permai Housing is planned as an integrated residential areas. This research was conducted in the area of Bumi Tamalanrea Permai Housing scenic Makassar City, which to know the process of the development of commercial functions and factors - factors that influence the development of the commercial functions in the area of Bumi Tamalanrea Permai Housing Makassar. From the results of this study found that the process of development of commercial functions in the area of Bumi Tamalanrea Permai Housing Makassar physically follow the main line of residential complexes and public transportation lines. While the stages of the process starting from the momentum trigger commercial buildings that shop, then going miss-stakeholder interaction, especially the government and Perumnas organizer, which was followed by increased access and facilities then chances trying to get better so came the commercial hierarchy. While commercial developments in the area of Perumnas Bumi Tamalanrea Permai is influenced by three main factors: the increase in the value space, space control is weak, and the chances of space utilization. Increasing the value associated with space facility and access as well as commercial hierarchy. weakly related to the control room mis-stakeholder interaction in this case the government, Perumnas organizer and private developers. While the opportunities associated with the momentum space utilization trigger commercial buildings and business opportunity society. From three factors that controlling space, the most dominant factor to influence the future of commercial functions